IDENTIFIKASI PRILAKU PENCEGAHAN SKABIES PADA SANTRIWAN DI PONDOK PESANTREN TARBIYATUL MUSTAFID - Supriyadi; Dewi Nur Sukma Purqoti; Zaenal Arifin (CV. ALIM'SPUBLISHING, 2024)
Scabies is a worldwide disease with varying prevalence as it can affect all socioeconomic classes, ages, races, and genders, scabies is a significant disease for public health as it is a major cause of global morbidity and mortality. Objective: Identify scabies prevention behavior in students. Research method: descriptive research using a cross sectional approach. The sample in this study was 44 respondents, Data collection method using questionnaires. Results: most scabies prevention behavior in students was in the less category, namely 86.3% (38 students). Conclusion: There is still a large percentage of scabies prevention behavior in students so that appropriate interventions are needed to increase student knowledge.